2011
DOI: 10.1007/s00464-011-2071-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of laparoscopic surgery for advanced transverse and descending colon cancer: a single-center experience

Abstract: BackgroundThe role of laparoscopic surgery in management of transverse and descending colon cancer remains controversial. The aim of the present study is to investigate the short-term and oncologic long-term outcomes associated with laparoscopic surgery for transverse and descending colon cancer.MethodsThis cohort study analyzed 245 patients (stage II disease, n = 70; stage III disease, n = 63) who underwent resection of transverse and descending colon cancers, including 200 laparoscopic surgeries (LAC) and 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
1
33
2
1
Order By: Relevance
“…Table 5 summarizes the intraoperative outcomes of LR and OR [7,[9][10][11][12][13][14]. While most studies already published in the literature report a significantly longer operative time in the group of patients who had undergone LR than OR, [7,11,13], we did not observe significant differences between the two groups, most likely because almost all LR were performed by a single surgeon (M.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Table 5 summarizes the intraoperative outcomes of LR and OR [7,[9][10][11][12][13][14]. While most studies already published in the literature report a significantly longer operative time in the group of patients who had undergone LR than OR, [7,11,13], we did not observe significant differences between the two groups, most likely because almost all LR were performed by a single surgeon (M.…”
Section: Discussionmentioning
confidence: 86%
“…This variable was not evaluated in the other studies which, instead, reported mean proximal and distal resection margins, with no significant differences between the two approaches [7,9,[11][12][13][14]. Only Kim et al [10] found a mean distal margin of 12.5 cm in the LR versus 9.2 cm in the open surgery group (p \ 0.05).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…33,34 In the surgical procedures for obstructive colorectal cancers, the distended bowel is thought to restrict the appropriate surgical field, and the fragile bowel can be a risk factor for intraoperative injuries. In the present study, laparoscopic surgery was intended for 7 patients according to our tumor criteria, and all of these surgeries could be carried out without conversion to open surgery.…”
Section: Surgical Outcomes Following Sems Placementmentioning
confidence: 99%
“…[1][2][3] However, the impact of several factors, such as obesity and transverse colon cancer, on the outcomes of laparoscopic colectomy poses some technical problems. [4][5][6][7] Patients with transverse colon cancer were often excluded from previous randomized controlled trials because it was difficult to determine the appropriate extent of lymph node dissection, and because the technical difficulties depend on the identification and lymph node dissection around the middle colic vessels, which have a variable anatomy. [5][6][7][8][9] The recent development of multidetector computed tomography (MDCT) has made it possible to perform three-dimensional CT angiography (3DCTA).…”
mentioning
confidence: 99%